Coarse-Grained Quantum Theory of Organic Photovoltaic Devices - Sánchez, Fernando (Nanomaterials (Basel), 2021)
Understanding the exciton dissociation process in organic solar cells is a fundamental issue for the design of high-performance photovoltaic devices. In this article, a parameterized quantum theory based on a coarse-grained tight-binding model plus non-local electron-hole interactions is presented, while the diffusion and recombination of excitons are studied in a square lattice of excitonic states, where a real-space renormalization method on effective chains has been used. The Hamiltonian parameters are determined by fitting the measured quantum efficiency spectra and the theoretical short-circuit currents without adjustable parameters show a good agreement with the experimental ones obtained from several polymer:fullerene and polymer:polymer heterojunctions. Moreover, the present study reveals the degree of polymerization and the true driving force at donor-acceptor interface in each analyzed organic photovoltaic device.